Research on Driving Mechanism of Ecological Industry for Ecological Civilization in the Karst Rural Area - Huiqiong Huang; Kangning Xiong; Jiawang Yan; Yongyao Li (Agriculture)
It is crucial to clarify the relationship between ecological industry development and ecological civilization construction, as well as their driving forces, to promote high-quality local development. The ecological environment of the karst region is fragile, and it faces a contradiction between ecological preservation and economic advancement. Coordinating the relationship between economic development and ecological protection is crucial for achieving sustainable development in rural karst regions. This study identified karst characteristics in Guizhou province, China, by constructing an index system for ecological industry development and civilization construction. It employed the entropy weight method to calculate a comprehensive score and utilized a coupling coordination model to analyze interactions and symbiotic coordination. Finally, a linear regression analysis model was employed to analyze the impact of ecological industrial development on the construction of ecological civilization. The results indicate the following: (1) The ecological industry and ecological civilization construction levels exhibited a relatively stable growth trajectory across three research areas from 2011 to 2021, with the ecological civilization construction index outperforming the ecological industry development index. (2) The correlation analysis indicated a relationship between the two indices in the research areas, and the divergence trend among the three research areas rose in a uniform direction, indicating a strong positive correlation between the two indices. From the perspective of the coupling degree (C), the degree of coupling between ecological industry and ecological civilization construction in the three research areas exceeded 0.9, indicating a high level of coordination. This suggests that ecological civilization construction and ecological industry in these research areas are effectively coordinated and exist in a state of harmonious co-promotion. There were differences from the coupling coordination degree (D) perspective, but they increased in the three research areas. (3) The regression analysis results indicate that the per capita agricultural output value, per capita forestry output value, per capita forage industry output value, industrial solid waste utilization rate, energy consumption per unit of GDP, tourism income, rocky desertification level, and proportion of the labor force population with a high school education or higher significantly contribute to the development of ecological civilization. The per capita forestry output value greatly advances ecological civilization, significantly enhancing ecological culture and security. The coefficients are 0.0354 and 0.0393, respectively, indicating that a 1% rise in the per capita forestry output value results in increases of 0.0354% and 0.0393% in the ecological culture and security indices.